One, Two and Three Photon Absorption in Atomic Hydrogen - Shrestha, Nilam; Nakarmi, Jeevan J (Nepal Journal of Science and Technology, 2012)
Non relativistic, semi-classical in dipole approximation, based on time dependent Schrodinger equation under the framework of perturbation theory, three different absorption processes in hydrogen atom are studied and calculated transition matrix element from an initial state to final state. DOI: http://dx.doi.org/10.3126/njst.v12i0.6520 Nepal Journal of Science and Technology 12 (2011) 324-329